Glycaemic abnormalities induced by small molecule tryosine kinase inhibitors: a review - Mugiya, Takudzwa; Mothibe, Mamosheledi; Khathi, Andile; Ngubane, Phikelelani; Sibiya, Ntethelelo (Frontiers in Pharmacology, 2024)
In light of the expected increase in the prevalence of diabetes mellitus due to an aging population, sedentary lifestyles, an increase in obesity, and unhealthy diets, there is a need to identify potential pharmacological agents that can heighten the risk of developing diabetes. Similarly, it is equally important to also identify those agents that show blood glucose-lowering properties. Amongst these agents are tyrosine kinase inhibitors used to treat certain types of cancers. Over the last two decades, there has been an increase in the use of targeted chemotherapy for cancers such as renal cell carcinoma, chronic leukaemia, and gastrointestinal stromal tumours. Tyrosine kinase inhibitors have been at the forefront of targeted chemotherapy. Studies have shown that tyrosine kinase inhibitors can alter glycaemic control and glucose metabolism, with some demonstrating hypoglycaemic activities whilst others showing hyperglycaemic properties. The mechanism by which tyrosine kinase inhibitors cause glycaemic dysregulation is not well understood, therefore, the clinical significance of these chemotherapeutic agents on glucose handling is also poorly documented. In this review, the effort is directed at mapping mechanistic insights into the effect of various tyrosine kinase inhibitors on glycaemic dysregulation envisaged to provide a deeper understanding of these chemotherapeutic agents on glucose metabolism. Small molecule kinase inhibitors may elicit these observed glycaemic effects through preservation of β-cell function, improving insulin sensitivity and insulin secretion. These compounds bind to a spectrum of receptors and proteins implicated in glucose regulation for example non-receptor tyrosine kinase SRC and ABL. Then receptor tyrosine kinase EGFR, PDGFR, and FGFR.